Object and apparition : envisioning the Christian divine in the colonial Andes - Stanfield-Mazzi, Maya Selama, 1972- (The University of Arizona Press, 2013)
"Based on thorough archival research combined with stunning visual analysis, Maya Stanfield-Mazzi demonstrates that Andeans were active agents in Catholic image-making and created a particularly Andean version of Catholicism. Object and Apparition describes the unique features of Andean Catholicism while illustrating its connections to both Spanish and Andean cultural traditions"--Provided by publisher.